Otoczenie ekonomiczne przedsiębiorstw hodowlano-nasiennych - Gołębiowski, Bogusław (The Economic Surroundings of Firms of Plant Raising, 2006)
In the article the author presents eight factors from the economic surroundings and their potential power of the influence on the performance of firms from the line of plant raising. The research was done in April 2005. The author used the analysis of continuity of the surroundings in it.From the analysis of continuity of the economic surroundings one can ascertain that analysed factors with different can by force bear on the vitality of the line of the plant raising. An only leading factor concerning the potentially large power of the affirmative influence is the height of the level of first-hand surcharges to the farming production. The potentially large by force negative influence is characterized by the negative tendency of development in the profitability from the leadership of the agricultural activity and the process of the height of the standard of prices on resources to the farming production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 251-256